The efficacy of augmented reality exposure therapy in the treatment of spider phobia—a randomized controlled trial - Jurcik, Tomas; Zaremba-Pike, Svetlana; Kosonogov, Vladimir; Mohammed, Abdul-Raheem; Krasavtseva, Yulia; Sawada, Tadamasa; Samarina, Irina; Buranova, Nilufar; Adu, Peter; Sergeev, Nikita; Skuratov, Andrei; Demchenko, Anastasia; et al. (Frontiers in Psychology, 2024)
Recently, the evidence for the use of Augmented Reality (AR) in treating specific phobias has been growing. However, issues of accessibility persist, especially in developing countries. The current study examined a novel, but relatively simple therapist guided smartphone-based AR Exposure Treatment (ARET) of spider phobia. Participants who reported symptoms of Arachnophobia were randomized into one of three comparison groups: ARET (n=20), traditional in vivo exposure therapy (IVET; n=18) and a waitlist control group (n=17). Behavioral approach, subjective symptom measures, and galvanic skin response were assessed pre-and post-treatment. The study was concluded with a one-month follow up assessment. Results indicated that both treatment groups showed statistically significant and clinically meaningful improvements in behavioral approach at post-test that were maintained at one month follow-up, compared to the wait-listed group. Moreover, the treatment groups demonstrated significant improvements in subjective symptom report at 1-month follow up. Given its utility and potential accessibility, our findings suggest that future AR evaluation research could be conducted in therapy settings with minimal resources.• We developed and tested a therapist guided Smartphone App for Augmented Reality Exposure Therapy (ARET) of Spider Phobia in a middle-income country • We completed a Randomized Control Trial comparing ARET to In Vivo Exposure Therapy (IVET) and a waitlist control group • ARET and IVET produced similar symptom and behaviour approach improvements compared to the control group • ARET may be an efficacious treatment in settings with limited resources.